Clinical Applications of Three-Dimensional Echocardiography - Vinall, Maria (MD Conference Express, 2010)
This article discusses real-time 3D echocardiography and its uses for evaluating for evaluating tumors of the heart and great vessles, selecting optimal surgical approaches prior to the remoal of intracardiac masses, during mitral valve stenosis intervention, and for viewing the mitral valve in relation of mitral regurgitation.